Toward unraveling molecular grammars for dsRNA-binding proteins: substrate recognition to binding mechanisms - Jeon, Jaemin; Kim, Yoosik (BMB reports, 2025)
Long double-stranded RNAs (dsRNAs) are recognized by innate immune response proteins, thereby initiating the integrated stress response. As these RNAs adopt an A-form helical structure, immune sensors recognize dsRNAs primarily based on their structural features, such as the length of the doublestranded stretch and the triphosphate at the 5' end, rather than on specific sequences. This structure-dependent, sequenceindependent mode of RNA recognition is also characteristic of many dsRNA-binding proteins (dsRBPs). Consequently, multiple dsRBPs share a common pool of dsRNA substrates, leading to a complex regulatory network in which proteins modulate each other's activation status and signaling activities. With the development of advanced analytical techniques capable of studying RNA sequences and structures at single-nucleotide resolution, research into dsRNA-protein interactions has advanced significantly. This review discusses the long dsRNAinteracting dsRBPs encoded in the human genome, their RNA substrates, recognition mechanisms, and the downstream effects of protein-RNA interactions, with the aim of deepening our understanding of dsRNA recognition and signaling. [BMB Reports 2025; 58(11): 451-466].